Srečevanja besede in glasbe - Troha, Gašper (Primerjalna književnost, 2015)
The article deals with a radio play The Return of Cortes by Andrej Hieng that was later on rewritten into an opera libretto. Through a comparative analysis of both texts and theses of Theodor Adorno about bourgeois opera it tries to detect features of an opera genre in the libretto by Pavel Šivic.
Keywords: Hieng, Andrej, 1925-2000; "Cortesova vrnitev"; Šivic, Pavel, 1908-1995; književnost in glasba; slovenska dramatika; eksistencializem; existentialism; radijske igre; glasbene predelave; opere; operni libreti